Reduction-based creative telescoping for fuchsian D-finite functions. (March 2018) - Chen, Shaoshi; van Hoeij, Mark; Kauers, Manuel; Koutschan, Christoph
Abstract: Continuing a series of articles in the past few years on creative telescoping using reductions, we adapt Trager's Hermite reduction for algebraic functions to fuchsian D-finite functions whose singularities have real exponents. We develop a reduction-based creative telescoping algorithm for this class of functions, thereby generalizing our recent reduction-based algorithm for algebraic functions, presented at ISSAC 2016.